2011
DOI: 10.1088/0957-4484/22/31/315711
|View full text |Cite
|
Sign up to set email alerts
|

Size-selecting effect of water on fluorescent silicon clusters

Abstract: Silicon clusters were produced by gas aggregation in vacuum and co-deposited with water vapour onto a cold target where the water vapour froze. Melting of the ice yielded fluorescent silicon nanoparticles suspended in water which were investigated by photoluminescence spectroscopy (PL) and atomic force microscopy (AFM). The PL spectrum showed a prominent band at 420 nm and other, less intense bands at shorter wavelengths. No fluorescence was observed below 275 nm. The shortest wavelength observed was related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Superlattices are regularly observed in HOPG and form due to interference 25 (Moiré) patterns formed when the top sheet of graphene is rotated with respect to the underlying crystal [13,14]. The same Moiré patterns are observed in epitactic graphene on Ruthenium and Iridium substrates.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Superlattices are regularly observed in HOPG and form due to interference 25 (Moiré) patterns formed when the top sheet of graphene is rotated with respect to the underlying crystal [13,14]. The same Moiré patterns are observed in epitactic graphene on Ruthenium and Iridium substrates.…”
Section: Introductionmentioning
confidence: 73%
“…The resulting solution was found to contain a stable phase of 45 silicon nanoparticles with a narrow size distribution centred at 1.3 nm. Analysis of this size distribution revealed that the nanoparticles had been produced entirely from the silicon atoms accompanying the cluster beam [25]. The produced particles showed stable luminescence over a period of 3 months [23], further measurements showing that fluorescence remains stable over years, in-50 dicating that the particles are chemically stable and have weak inter-particle reactions.…”
mentioning
confidence: 88%
“…Atomic force microscopy in noncontact and constant force mode of cluster films produced by drop-casting colloidal solution onto freshly cleaved HOPG showed uncovered regions of graphite, and agglomerated monolayers, as well as double layers, of clusters (Torricelli et al, 2011). The height of the monolayers reflected the difference of the tip-HOPG and tip-cluster forces, and hence cannot be taken as a measure of cluster height.…”
Section: Blue Fluorescencementioning
confidence: 96%
“…When the photoexcitation wavelength was decreased from 310 to 240 nm, the wavelength of the fluorescent band remained at 420 nm; however, additional fluorescence bands appeared in the UV region (von Haeften et al, 2010a,b;Torricelli et al, 2011). When the clusters were embedded in liquid ethanol and isopropanol, the fluorescence wavelength shifted to 365 and 380 nm, respectively (Galinis et al, 2012b).…”
Section: Blue Fluorescencementioning
confidence: 99%
“…After deposition, the ice was melted and a silicon nanoparticle-containing suspension was collected in a dish ). Silicon nanoparticles produced with this technique show a number of extraordinary properties: the average particle size is 1 nm in diameter (Torricelli et al 2011), they emit intense fluorescence in the deep blue spectral range when exposed to UV light, and the fluorescence intensity does not degrade over time. The interaction with water was found to be critical for the development of fluorescent activity; silicon clusters that were produced in our apparatus and directly deposited on a substrate without the water vapour beam on did not show fluorescence.…”
Section: Introductionmentioning
confidence: 99%